Assessment of factors implicated in bone fusion after percutaneous endoscopic lumbar intervertebral fusion - Zheng Huang; Xialin Li; Weihong Yi; Junfeng Gong; Yue Zhou; Yu Tang (Acta Orthopaedica et Traumatologica Turcica)
Objective: Lumbar spinal fusion is a common procedure for treating spinal degenerative diseases. Percutaneous endoscopic lumbar interbody fusion (PELIF) is a minimally invasive technique that has gained popularity. However, the factors influencing fusion success rates after PELIF have not been well-studied.